The Implementation of Scientific Approach to Increase Mathematics Understanding Ability on Algebraic Derivative Materials - Muhamad Taufik Fathurrohman; Asep Ikin Sugandi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2023)
Referring to the objectives of learning mathematics and NCTM, one of the abilities that must be developed is the ability to understand mathematics. The importance of having the ability to understand mathematics includes this ability listed in the learning of mathematics in the 2006 KTSP mathematics curriculum and the 2013 curriculum. This study aims to examine the increased understandingÂ Â of the material concept of derivatives of algebraic functions in class XI high school students. This type of research is classroom action research. This research was conducted on class XI high school students for the 2020/2021 academic year, consisting of 16 students. The instrument used is a test of students' mathematical understanding abilities, in the form of 6 questions that focus more on students' understanding abilities regarding the derivative of algebraic functions; observation sheet for teachers and students to see the condition of the implementation of the action. This study shows that students' mathematical understanding abilities have increased as seen from the questions tested on each test with an increase in mastery from initially 31.25% to 56.25%. The results of this study indicate that the application of a scientific approach can improve the comprehension skills of class XI students on material derived from algebraic functions.